O traje medieval português e sua função alegórica no Auto da Barca do Inferno e no Auto da Alma de Gil Vicente - Souza, Érica Fernanda Brasil Carosia Paulino de (2011)
This dissertation examines the role of the allegorical medieval costume Portuguese, Auto da Barca do Inferno (1517) and Auto da Alma (1518) Gil Vicente. As specific objectives, we demonstrate the relationship between clothing and the characters, explain the symbolism of each piece of clothing, and elucidate the Vincentian context, through the clothing, the conflict between the sacred and the profane, the ideological concepts of the sixteenth century Christians In two acts of religious playwright Portuguese. We point out relevant data from the clothing of the sixteenth century, as well as the theoretical background on allegory. We apply the concept, through clothing, to elucidate the conflict between salvation and damnation of the characters in the context of the pieces. We explain the issue from two allegorical modes stylistic or rhetorical allegory constructive (so to speak) and allegory interpretive or hermeneutic (way of understanding). Object of study by numerous researchers, the machine takes a critical look that demands a closer look. Establishes a visual language as relevant as verbal discourse. Reveals information. Expresses ideas. Represents the social and cultural changes. Allows interactions between society. It expresses identity and behavior. However, we observed that the clothing is not synonymous with acquittal or conviction, but joins the allegorical character of the works of playwright Portuguese, who always point to two conflicting realities: human and divine, the immanent and transcendent, individual ethics and social ethics